2006
DOI: 10.1159/000096689
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant as Salvage Therapy in Patients with Chemotherapy-Induced Nausea and Emesis Refractory to Prophylaxis with 5-HT<sub>3</sub> Antagonists and Dexamethasone

Abstract: Background: Despite prophylaxis with 5-HT3 antagonists and dexamethasone, nausea/emesis are common chemotherapy- induced toxicities. The aim of this trial was to evaluate the efficacy of adding the NK1 antagonist aprepitant in patients refractory to standard prophylaxis. Patients and Methods: Patients with significant nausea/vomiting despite prophylaxis with 5-HT3 antagonists and dexamethasone were eligible. Aprepitant was added to the same antiemetic regimen used during previous cycles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…It is important to emphasize that the number of analyzable patients treated by aprepitant is very small. Nevertheless, this is in line with results from a trial conducted by Oechsle et al [20] where aprepitant demonstrated significant activity in patients with nausea/vomiting refractory to prophylaxis with 5HT 3 antagonists and dexamethasone treated with cisplatin-based chemotherapy. The number of patients with nausea for > 4 days decreased from 71 to 12% (p < 0.001), and the number of those with emesis for > 2 days decreased from 77 to 0% (p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…It is important to emphasize that the number of analyzable patients treated by aprepitant is very small. Nevertheless, this is in line with results from a trial conducted by Oechsle et al [20] where aprepitant demonstrated significant activity in patients with nausea/vomiting refractory to prophylaxis with 5HT 3 antagonists and dexamethasone treated with cisplatin-based chemotherapy. The number of patients with nausea for > 4 days decreased from 71 to 12% (p < 0.001), and the number of those with emesis for > 2 days decreased from 77 to 0% (p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, another report has appeared noting improved antiemetic control with the addition of aprepitant in patients experiencing breakthrough emesis despite receiving prophylaxis with a 5-HT 3 antagonist and dexamethasone during their initial cycle of chemotherapy [25]. In 34 patients receiving a variety of chemotherapy regimens, the addition of aprepitant to the same antiemetic regimen used during the initial cycle resulted in an improved outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggesting that the mechanism of action of palonosetron may differ from that of other serotonin antagonists [22] could provide a rationale for additional activity with this agent. More recently, several studies [23,24] have documented antiemetic activity of the NK-1 antagonists in patients who did not achieve complete protection from emesis when treated with dexamethasone and a serotonin receptor antagonist alone.…”
Section: Refractory Emesis and Rescue Antiemeticsmentioning
confidence: 99%